Performance of Flow Through and Over Trapezoidal Gabion Weir (Journal of University of Babylon for Engineering Sciences, 2024)
Different upstream and downstream slopes of trapezoidal gabion were studied in open laboratory flume. The upstream flow depth and the discharge were investigated through laboratory experiments. Twelves models were tested in a laboratory flume. The experiment tests included three regimes of flow (Through flow, Transition Flow, and Overflow) under free flow conditions. The trapezoidal slopes were changed three times (1:1, 1:1.5, and 1:2). For each trapezoidal slope, gravel coarseness differed four degrees (1.13, 1.58, 2.19, and 2.27 cm). The analysis of experimental results showed that as material coarseness increased, the discharge pass through trapezoidal gabion weir increased from 17.5%. to 35.8%.  All models showed that discharge (Q) is related to the ratios of upstream height of water to length of weir (H/L) and the percentage of discharge is increase from 16% to 50% due to change side slopes from 1:1 to 1:2.The discharge coefficient is related to the (H/L , H/p and dm/H).The discharge coefficient increased with the increase in gravel coarseness (porosity) and increase the side slops from (1:1 to 1:2) also cause the coefficient of discharge increase. Two mathematical models for the water flow depth and the coefficient of discharge predicted for the three flow regimes are presented. The estimated and computed values showed a high degree of correlation.